LETHARGY AND HYPOTONIA IN A PRETERM NEONATE – USUAL SYMPTOM WITH UNUSUAL DIAGNOSIS OF MITOCHONDRIAL TRIFUNCTIONAL PROTEIN DEFICIENCY - KADIRVEL, KARTHIKEYAN; Davis, Liza; Sivapregassam, Ragasivamalini (Indian Journal of Case Reports, 2022)
Background: Methodical evaluation of a neonate with common clinical findings (hypotonia and lethargy) is important whenever it cannot be attributed to the frequent causes. This case report is on a preterm neonate with persistent hypotonia and metabolic acidosis was evaluated and diagnosed with mitochondrial trifunctional protein deficiency. Report: A preterm male baby second born to second degree consanguineous parents was found to have profound lethargy and hypotonia with severe metabolic acidosis despite the shock being corrected. Management: In spite of negative reports of first tier investigations for inborn errors of metabolism (IEM), baby was started on carnitine and biotin with strong clinical suspicion for IEM. Whole exome sequencing in the baby and Sanger sequencing in mother showed same gene mutation in HADHA gene suggesting mitochondrial trifunctional protein (MTFP) deficiency. He was started on special infant formula containing medium chain triglycerides along with breastfeeding. Conclusion: Early diagnosis and initiation of fat modified diet, avoiding catabolic stress situation and aggressive treatment during intercurrent illness can have satisfactory growth and development in the child.